Fly Ash as an Amendment Agent for Soil Fertility - Jala, Sudha (My University, 2006)
Coal is an exhaustible energy source, which plays a critical role in meeting the ever-increasing energy demands of countries around the world. Combustion of coal in thermal power stations produces a variety of residues viz. fly ash, bottom ash, flue gas desulfurization waste (scrubber sludge) and fluidized bed boiler waste and coal gasification ash. The physical, chemical and mineralogical characteristics of fly ash depend on a variety of factors such as composition of parent coal, combustion conditions, the efficiency and type of emission control devices and the disposal methods used. Fly ash is an amorphous mixture of ferroaluminosilicate minerals generated from combustion of ground or powdered coal at temperature ranging from 400-1500°C. It is composed predominantly of small, glassy, hollow particles with specific gravities ranging from 2.1 to 2.6. g cm"3. Physically, fly ash occurs as very fine particles having an average diameter of <10 lam, low to medium bulk density, high surface a~ea and light texture which are aggregated into micron and sub-micron .spherical particles, of size ranging from 0.01 to 100 mm, with smaller particles entrapped within large spheres. 90-99 of fly ash consists of Si, A1, Fe, Ca, Mg, Na and K. Major matrix elements in fly ash are Si and A1 together with significant percentage of K, Fe, Ca and Mg. Fly ash contains all naturally occurring elements and is substantially rich in trace elements like lanthanum, terbium, mercury, cobalt and chromium. Over 225 million tonnes of coal is being produced annually in India. The coal, which is of poor quality, generates on an average about 40 ash. In India over 100 thermal power stations are producing around 108 million tonnes of fly ash every year and it is expected to double by the year 2010. On account of its heterogenous nature fly ash has the potential to be used as a soil-ameliorating agent in agriculture and forestry. Field and greenhouse studies both indicate that many chemical constituents of fly ash may benefit plant growth and can improve agronomic properties of soil. Fly ash addition alters physical properties of soil such as texture, bulk density, water holding capacity and particle size distribution. The disposal of fly ash by conventional methods leads to degradation of arable land and contamination of the ground water. Therefore, development of proper technology for disposal of this solid waste in an eco-friendly manner becomes mandatory and to derive maximum benefit from its heterogenous nature since it is a storehouse of readily available plant macro and micronutrients. In conjunction with organic manure, microbial inoculants or fertilizers fly ash can be used to design a soil benefaction strategy, which would help in improving the properties of soil and enriching its nutrient status. Presence of almost all essential plant nutrients in ionic form and ameliorating effect on physical, chemical and microbial nature of the soil, makes fly ash an important input for biomass production especially on variously degraded soils and waste lands. The present thesis deals with "fly ash as an amendment agent for soil fertility". The work presented in the thesis deals with characterization of fly ash and soil from different sources and region. In addition to this the effect of fly ash on soil microbial activity was investigated in terms of biomass production, soil dehydrogenase activity and rate of carbon-dioxide evolution. A number of phosphate-solubilizing bacteria were isolated from fly ash amended soil and selected strain was transformed with lac Z marker followed by studies on its growth and proliferation in soil with and without fly ash. The effect of fly ash on growth of populus deltoides in nursery trail and established field plantations of Acacia auriculiformis and Eucalyptus tereticornis along with assessment of nutrient status of soil was studied. It was concluded that 12 to 18% fly ash helped in maintaining nutrient profile of soil and improving plant productivity.
Ph.D. Thesis. Supervised by..
Keywords: Soil-plant-microbe Interaction; Fly Ash Utilization; Plant Growth; Biotechnology; Environmental Sciences; Solid Waste Recycling